3D characterisation of surface topographies of wear debris collected from human knees for osteoarthritis study. (August 2019) - Wang, Meiling; Peng, Zhongxiao
Abstract: The surface topographies of wear debris found in human knees were collected at the nano-scale in their hydrated status using atomic force microscopy (AFM) and characterised quantitatively. As a result, the spatial ( Scl37 ) and functional ( Spk ) parameters were identified as potential early OA indicators to separate wear debris generated in normal knees from those in mild OA condition. The selected key hybrid parameter, Sdq, revealed significance in discriminating wear particles in the severe OA from those in the other conditions (i.e., normal and mild OA). The other selected parameters including the commonly used amplitude parameter Sa can help distinguish wear debris in normal and severe OA conditions. The 3D characterisations of wear debris provide a new approach for OA assessment. Highlights: AFM was used to study surface topographies of hydrated wear debris in human knees. Distinctive surface features were identified. Numerical descriptors to quantitatively characterise these features were selected.